2023
DOI: 10.1007/s00264-023-05989-2
|View full text |Cite
|
Sign up to set email alerts
|

Candida spondylodiscitis: a systematic review and meta-analysis of seventy two studies

Siegfried J. Adelhoefer,
Marcos R. Gonzalez,
Angad Bedi
et al.

Abstract: Objectives Knowledge of Candida spondylodiscitis is limited to case reports and smaller case series. Controversy remains on the most effective diagnostical and therapeutical steps once Candida is suspected. This systematic review summarized all cases of Candida spondylodiscitis reported to date concerning baseline demographics, symptoms, treatment, and prognostic factors. Methods A PRISMA-based search of PubMed, Web of Science, Embase, Scopus, and OVID Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…In total, 53 patients with a definite diagnosis of proven IFSD were retrospectively studied over 20 years. Except for the much higher overall one-year mortality rate (45.3%), the mean age (around 65) and male predominance were compatible with the studies previously reported [16,18,25,29]. Predisposing immunocompromised state was seen in about one-third of all the patients with IFSD involved and possessed one of the striking predictors for one-year mortality (50.0% vs. 17.2%, p = 0.011).…”
Section: Patient Characteristics and Clinical Manifestationssupporting
confidence: 88%
See 1 more Smart Citation
“…In total, 53 patients with a definite diagnosis of proven IFSD were retrospectively studied over 20 years. Except for the much higher overall one-year mortality rate (45.3%), the mean age (around 65) and male predominance were compatible with the studies previously reported [16,18,25,29]. Predisposing immunocompromised state was seen in about one-third of all the patients with IFSD involved and possessed one of the striking predictors for one-year mortality (50.0% vs. 17.2%, p = 0.011).…”
Section: Patient Characteristics and Clinical Manifestationssupporting
confidence: 88%
“…The overall mortality rate is around 20% [15,17]. Several risk factors for developing fungal spondylodiscitis were investigated, mainly related to immunocompromised states [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…Candida spp. spondylodiscitis (CS) is a rare manifestation of invasive candidiasis; only 89 cases of culture-confirmed CS have been reported so far, according to a recent meta-analysis [3]. Candida albicans spondylodiscitis was the most frequent species isolated and only six cases of C. parapsilosis were described [3].…”
Section: Introductionmentioning
confidence: 99%
“…According to a meta-analysis by Adelhoefer and colleagues, among the 89 included patients with CS, antifungal monotherapy was given in 58% of cases; the most commonly used antifungal agents were fluconazole (68%), amphotericin B (38%), and echinocandins (26%), and the median length of antifungal treatment was six months [3]. Surgical intervention was performed in 68% of cases, including 34% undergoing instrumented discectomy [3]. At a median follow-up of 12 months, 3% developed sepsis, 6% underwent revision, and 12% died of disease [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation